2023
DOI: 10.1002/fsn3.3609
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin protects against acetaminophen‐induced oxidative damage in liver through activation of the Keap1/Nrf2 signaling pathway

Wanhai Zhou,
Heng He,
Qin Wei
et al.

Abstract: Puerarin (Pue) is a kind of isoflavone compound extracted from Pueraria lobata, which has significant antioxidant activity. Excessive use of acetaminophen (APAP) can cause oxidative stress in the liver and eventually lead to acute liver injury. The purpose of this study was to investigate the protective effect and the mechanism of puerarin on APAP‐induced liver oxidative damage. In in vitro experiments, puerarin significantly increased the cell activity of HepG2 cells, reduced the ROS accumulation, alleviated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Keap1 acts as a negative regulator of Nrf2, inhibiting its nuclear translocation. The Nrf2 signaling pathway serves as the central regulator of oxidative stress responses within biological organisms, controlling the expression of various antioxidant response-related genes or enzymes [17]. When cells are damaged, Nrf2 is up-regulated and activates phase II enzymes, enhancing the cells' tolerance to oxidative stress [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keap1 acts as a negative regulator of Nrf2, inhibiting its nuclear translocation. The Nrf2 signaling pathway serves as the central regulator of oxidative stress responses within biological organisms, controlling the expression of various antioxidant response-related genes or enzymes [17]. When cells are damaged, Nrf2 is up-regulated and activates phase II enzymes, enhancing the cells' tolerance to oxidative stress [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in our laboratory has revealed that functional feed additives can improve the antioxidant capacity of weaned piglets by activating the Nrf2 signaling pathway and optimize their mitochondrial function, thus effectively reducing the oxidative damage of paraquat to the liver [16]. The Nrf2 signaling pathway plays a central regulatory role in the oxidative stress response in vivo, and it controls the expression of a variety of genes or enzymes related to antioxidants [17]. In the non-stressed state, Keap1 forms ubiquitin E3 ligase complexes with CULLIN3 (CUL3), resulting in the polyubiquitination of Nrf2, which is then rapidly degraded by the proteasome system.…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin, an iso avone compound extracted from pueraria root, has protective properties for heart and liver cells, as well as anti-in ammatory and anti-apoptotic effects (32,33,34). Recent studies have reported that it can promote osteoblast differentiation and mineralization, inhibit osteoblast apoptosis, and prevent bone loss (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%